Seismic Evaluation of Plan Asymmetry Effects in an Older Infill Framed Reinforced Concrete Building Structures - Aslam F. Mohammad; Marco Faggella; Rashid A. Khan; Sami U. Haq; Muhammad Saim (Engineering Reports)
ABSTRACT Several earthquake events revealed the severity of damage in reinforced concrete (RC) building structure mainly from the irregular placement of masonry infill and negligence of code compliant detailing provisions in structural components on building response. This study aims to evaluate the detrimental effects of nonuniform placement of infill panels in building structures constructed in regions susceptible to high seismic risk. Therefore, a finite element model (FEM) model of an older infilled frame RC building employed herein with various combinations of infill placement along with noncompliant detailing in structural components including bond‐slip effects in plastic region of frame components and the short column effects from frame infill interaction. Results are presented in terms of modal periods and confirm that the period obtained from theoretical or empirical models reported in literature provides a good estimate. Furthermore, the interstory drift ratio (IDR) at ultimate limit states obtained from nonlinear static and dynamic analyses depict the poor performance of in‐plan irregular configurations compared with the counterpart. Moreover, in irregular configurations, the roof displacement calculated from N2 and Extended N2 methods miscalculate the roof displacement obtained from nonlinear dynamic analysis and the difference in results increases from serviceability to ultimate limit states.